(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, comments on the formation of the element 是shì as a conjunction in the Chinese language are presented. Examples of its being a means of connecting horses and cattle are given with theoretical knowledge.